2018
DOI: 10.1016/j.ajpath.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-Binding Protein Involved in Hyaluronan Depolymerization Is Up-Regulated and Involved in Hyaluronan Degradation in Human Osteoarthritic Cartilage

Abstract: Hyaluronan (HA)-binding protein involved in HA depolymerization (HYBID), also called cell migration-inducing protein (CEMIP; alias KIAA1199), plays a key role in the degradation of HA in skin and arthritic synovial fibroblasts, but its functions in osteoarthritic (OA) cartilage remain elusive. Here, we investigated the expression and roles of HYBID in human OA cartilage. HYBID was highly expressed by chondrocytes in the HA-depleted area of OA cartilage, and HYBID immunoreactivity was correlated with Mankin sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…These data suggest that CEMIP could have a significant role in the molecular disturbance encountered at an early stage of the disease. In accordance, very recently Shimizu et al 35 , showed that CEMIP expression correlated with Mankin score of OA patients.…”
Section: Discussionsupporting
confidence: 79%
“…These data suggest that CEMIP could have a significant role in the molecular disturbance encountered at an early stage of the disease. In accordance, very recently Shimizu et al 35 , showed that CEMIP expression correlated with Mankin score of OA patients.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, we explored the mechanism of CEMIP regulation in chondrocytic cells. Shimizu et al reported that CEMIP expression in OA chondrocytes was induced by TNFα, but not by TGF-β1, IL-1α, histamine, insulin-like growth factor (IGF)-1, vascular endothelial growth factor (VEGF)-165, basic fibroblast growth factor (bFGF), or prostaglandin E2 (PGE2) [20]. Interestingly, our results demonstrated that IL-1β induced CEMIP mRNA expression in OUMS-27 cells.…”
Section: Discussionsupporting
confidence: 39%
“…Previous studies have demonstrated that HA synthesis by HAS (hyaluronan synthase) was involved in OA development [19]. HYAL-1, HYAL-2, and CD44 were found to be increased in OA chondrocytes compared to normal cartilage, but their gene knockdown did not have a significant effect on HA degradation [20]. These data suggested that CEMIP might be associated with HA metabolism in OA cartilage.…”
Section: Discussionmentioning
confidence: 82%
“…This was seen in cells but preferentially in TEX. Additional proteins selectively or preferentially coimmunoprecipitating with CD44v6 that could assist integrin activation are CLTC (clathrin heavy chain 1) and CSPG4 (chondroitin sulfate proteoglycan 4) [57, 58]. CD44v6 also associates with LGR5/LGR6, which supports Wnt binding and downstream signaling activation [12, 36].…”
Section: Discussionmentioning
confidence: 99%